International migration and global crisis: a historical- structuralism approach - Cervantes, Carmen Lilia (Universidad Autónoma del Estado de México, 2019)
This paper presents a conceptual framework for analyzing international migration in a historical context and particularly in a time of recurrent economic and financial crises. The analysis starts with a panorama of migrations in the global era and the presentation of theoretical references which link globalization with the configuration of international migratory movements. The accumulation pattern is presented as a category of analysis and a review is made of the evolution of the historical stages of capitalist accumulation in order to the migratory phenomenon.